High-density SNP association study and copy number variation analysis of the AUTS1 and AUTS5 loci implicate the IMMP2L-DOCK4 gene region in autism susceptibility. - Maestrini, E; Pagnamenta, A; Lamb, J; Bacchelli, E; Sykes, N; Sousa, I; Toma, C; Barnby, G; Butler, H; Winchester, L; Scerri, T; Minopoli, F; et al. (2010)
Autism spectrum disorders are a group of highly heritable neurodevelopmental disorders with a complex genetic etiology. The International Molecular Genetic Study of Autism Consortium previously identified linkage loci on chromosomes 7 and 2, termed AUTS1 and AUTS5, respectively. In this study, we performed a high-density association analysis in AUTS1 and AUTS5, testing more than 3000 single nucleotide polymorphisms (SNPs) in all known genes in each region, as well as SNPs in non-genic highly conserved sequences. SNP genotype data were also used to investigate copy number variation within these regions. The study sample consisted of 127 and 126 families, showing linkage to the AUTS1 and AUTS5 regions, respectively, and 188 gender-matched controls. Further investigation of the strongest association results was conducted in an independent European family sample containing 390 affected individuals. Association and copy number variant analysis highlighted several genes that warrant further investigation, including IMMP2L and DOCK4 on chromosome 7. Evidence for the involvement of DOCK4 in autism susceptibility was supported by independent replication of association at rs2217262 and the finding of a deletion segregating in a sib-pair family.